The Discourse of Islam in Populism Movement - Shalihin, Nurus; Yusuf, M; Hulwati, Hulwati (Journal of Pragmatics and Discourse Research, 2023)
This article aims to examine the discourse of Islam within the Islamic populism movement. The study of Islamic populism continues to receive attention in recent years. With remarkable developments, this article aims to explore the concept of Islamic populism within ChatGPT as a human intelligence platform that has been formatted into a technological program. This study is a qualitative research using a literature review approach. All data comes from the text-based ChatGPT, resulting from systematically formulated questions input on January 9th, 2023. Findings from ChatGPT's readings on Islamic populism provide information that the movement lacks a single meaning and definition. Islamic populism adapts to religious issues and sentiments, depending on the context in which it develops